Preclinical Animal Modeling in Medicine - Purevjav, Enkhsaikhan; Pierre, Joseph F.; Lu, Lu (IntechOpen, 2022)
The results of preclinical animal research have been successfully implemented in various medical and biological practices. The use of animals in medicine is based on significant anatomical, physiological, and molecular similarities between humans and animals. Particularly, mammals that have vast biological commonalities with humans represent not only a valuable model to explore the mechanisms of varied human diseases, but also to define new diagnostic and treatment strategies. This book covers broad but important aspects of animal modeling for scientific medicine as well as for translational systems and biological sciences. Alternative methods such as cell culture and in vitro experiments that do not require the sacrifice of an animal are encouraged for scientific and medical studies.